2018
DOI: 10.1002/ecs2.2212
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and resilience: ten years of monitoring shrub and prairie communities in Orange County, CA, USA

Abstract: Mediterranean‐climate natural systems have high ecological value, yet the extent of their cover has diminished greatly due to changes in land use. Other stressors, ranging from intense short‐term disturbances such as wildfire to more gradual events such as extended drought and continuous pressures including competition with invasive species, test the resistance and resilience of community composition and structure. Data from long‐term monitoring provided an opportunity to evaluate the responses of three Southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 82 publications
(178 reference statements)
0
10
0
Order By: Relevance
“…Moreover, most previous southern California post-fire research followed large-scale burns in 1978 and 1993, before the onset of recent intense drought conditions (but see [34]). While a few studies document the importance of water availability to native shrubs in sage scrub [35], none have yet developed statistical models that link rainfall with shrub demographic rates.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most previous southern California post-fire research followed large-scale burns in 1978 and 1993, before the onset of recent intense drought conditions (but see [34]). While a few studies document the importance of water availability to native shrubs in sage scrub [35], none have yet developed statistical models that link rainfall with shrub demographic rates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the importance of time lags between precipitation occurrence and vegetation response have often indicated that the legacy of precipitation in prior years influences productivity and other ecosystems processes in the present (Bunting et al., 2017; Kimball et al., 2018; Ogle et al., 2015; Sala et al., 2012). We observed this type of legacy effect in the Landsat record (Figure ), and that the importance of precipitation legacy increased at longer timesteps, underscoring the importance of long‐term precipitation regime in driving vegetation trends.…”
Section: Discussionmentioning
confidence: 99%
“…5B ). Thus, we predict the distance from a patch of the highly invasive B. nigra ( Bell and Muller 1973 ) may have a greater impact on seed set in wet than in drought years, all else equal, as these southern California coastal sage scrub communities swing between precipitation extremes ( Kimball et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%